In vitro cultures of Vitis vinifera L. cv. Chardonnay synthesize the phytoalexin nerolidol upon infection by Phaeoacremonium parasiticum - Escoriaza, Maria Georgina (2013)
This study investigated terpene synthase (TPS) activity and terpene antifungal metabolites in calluses and cell suspension cultures of Vitis vinifera cv. Chardonnay infected with Phaecremonium parasiticum, one of the fungi associated with the grapevine diseases known as “hoja de malvón” and young vine decline. The highest TPS activity, assessed as tritiated farnesyl pyrophosphate ([1-3H]-FPP) transformed into hexane-soluble radioactive products, was observed in both inoculated calluses and cell suspension cultures (CSC). When tested in inoculated cell suspension cultures the TPS activity was maximal at 8 h after [1-3H]-FPP application and then declined; this was associated with a temporary increase of the sesquiterpene nerolidol. Grape calluses produced: α-pinene, nerolidol and squalene whether or not they were inoculated with Pm. parasiticum. As fungal amount raised the relative concentration of α-pinene and nerolidol increased in respect to squalene in calluses. The TPS activity and nerolidol and α-pinene accumulation was correlated with the increase in the amount of inoculated fungus. Of the mentioned metabolites mainly squalene was identified from extracts of fungal cultures. The results suggest that the response of grapevine tissues to Pm. parasiticum is dependent on the pathogen concentration and is characterized by increasing TPS activity through de novo synthesis.